2016
DOI: 10.1002/jobm.201600358
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of bacteria associated with different mosses by 16S rRNA and 16S rDNA sequencing

Abstract: To understand the differences of the bacteria associated with different mosses, a phylogenetic study of bacterial communities in three mosses was carried out based on 16S rDNA and 16S rRNA sequencing. The mosses used were Hygroamblystegium noterophilum, Entodon compressus and Grimmia montana, representing hygrophyte, shady plant and xerophyte, respectively. In total, the operational taxonomic units (OTUs), richness and diversity were different regardless of the moss species and the library level. All the exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Among these bacterial species, the Proteobacteria had the highest degree of enhancement. Therefore, compared to traditional bacterial culture methods, the 16S-rDNA PCR amplification technology exhibited a few remarkable merits in screening and identifying bacteria, including explicit and existent bacterial colonies, relatively higher abundance, undifferentiated bacterial colony growth, and higher efficacy [27].…”
Section: Discussionmentioning
confidence: 99%
“…Among these bacterial species, the Proteobacteria had the highest degree of enhancement. Therefore, compared to traditional bacterial culture methods, the 16S-rDNA PCR amplification technology exhibited a few remarkable merits in screening and identifying bacteria, including explicit and existent bacterial colonies, relatively higher abundance, undifferentiated bacterial colony growth, and higher efficacy [27].…”
Section: Discussionmentioning
confidence: 99%
“…They are found in both monocotyledon and dicotyledon species (Ryan et al 2008). The colonisation of endophytic bacteria in ferns, algae and bryophytes has already been described (Colombo 1978;Hollants et al 2011;Shcherbakov et al 2013;Liu et al 2014;Das et al 2017a;Tian & Li 2017;Mahlangu & Serepa-Dlamini 2018). All groups of plants ranging from seagrasses (Marhaeni et al 2011;Garcias-Bonet et al 2012) to large trees (Shen & Fulthorpe 2015;Puri et al 2017) harbour endophytic bacteria.…”
Section: Diversity Of Endophytic Bacteriamentioning
confidence: 97%
“…As the proportion of sphagnum replacing peat increases, Massilia gradually supplanted Dokdonella as the predominant denitrifying bacterial genus. Previous studies have identified Rhodanobacter as a genus with a fully denitrifying capacity that is present in a variety of habitats [35,36], while Massilia is the common dominant genus among all the mosses tested based on the previous library of research [37]. Therefore, the substitution of peat with sphagnum can alter the structure and composition of microbial communities in the substrate and enhance the denitrification potential through increasing the dominance of Massilia.…”
Section: Microbial Mechanisms Of N 2 O Production and Consumptionmentioning
confidence: 99%